Relationship Between Knowledge, Attitude, and Practice of General Practitioners Regarding Diabetic Retinopathy Screening Among Diabetes Mellitus Patients in Primary Healthcare Centers on Lombok Island - I Kadek Ari Sanjaya; Monalisa Nasrul; Ni Nyoman Geriputri (Jurnal Biologi Tropis, 2026)
Diabetic retinopathy (DR) is a common complication of diabetes and a preventable cause of blindness through early detection. General practitioners (GPs) play a crucial role in DR screening, yet field practices often do not align with their level of knowledge. This study analyzed the relationship between knowledge and attitudes of GPs and their DR screening practices in primary healthcare centers (Puskesmas) across Lombok Island. This cross-sectional study involved 45 GPs selected through purposive sampling. Data were collected using structured questionnaires assessing knowledge (36 items), attitude (8 items), and practice (8 items). Pearson’s correlation test was used for data analysis. Most respondents had good knowledge (86.6%) and all demonstrated positive attitudes toward DR screening. However, only 13.3% showed good screening practices. Pearson’s test revealed no significant relationship between knowledge and practice (r = 0.105; p = 0.494) nor between attitude and practice (r = –0.111; p = 0.494). Low implementation of screening was influenced by limited availability of equipment (77.7% lacked an ophthalmoscope), insufficient training (71.1%), high workload, and low confidence in interpreting funduscopic findings. Despite adequate knowledge and positive attitudes, GPs’ screening practices for DR remain low and are not associated with these factors. Screening behavior is more strongly influenced by structural and systemic barriers. Improving early detection requires adequate equipment, practical training, and strengthened referral pathways.